Pharmacokinetics, Urinary Excretion, and Pharmaco-Metabolomic Study of Tebipenem Pivoxil Granules After Single Escalating Oral Dose in Healthy Chinese Volunteers - Li, Zeyun; Su, Mei; Cheng, Weiyan; Xia, Jueyu; Liu, Shuaibing; Liu, Ruijuan; Sun, Suke; Feng, Luyao; Zhu, Xueya; Zhang, Xiaojian; Tian, Xin; Qu, Lingbo (Frontiers in Pharmacology, 2021)
Tebipenam pivoxil (TBPM-PI), an oral carbapenem antibiotic, has shown special advantages in pediatric infections and was in urgent need in China. Although pharmacokinetics, urinary excretion and metabolites information of its active form Tebipenam (TBPM) has been reported. However, ethnic difference may exit in Chinese population. By now, no systematic pharmacokinetics, urinary excretion, metabolites or safety information has been revealed in Chinese population. The purpose of present work is to investigate abovementioned information of TBPM-PI Granules after oral single ascending doses of 100, 200 and 400 mg in Chinese volunteers. Based on pharmacokinetics study, urine pharmaco-metabolomics analysis was conducted to reveal metabolomic interruptions and metabolites information. The study design was a single center, open-label, randomized, single-dose pharmacokinetic study of 36 healthy volunteers (half male and half female). Time to maximum concentration (Tmax) was reached at 0.50, 0.50 or 0.67 h for 100, 200 or 400 mg. Linear pharmacokinetic characteristic of maximum plasma concentration (Cmax) was detected over 100-200 mg. Area under the concentration time curve (AUC) was proportional to the dose in the range of 100-400 mg. Maximum urinary excretion rate was detected at 0-1 or 1-2 h for dose of 100 or 200-400 mg. Cumulative amount of TBPM excreted in urine by 24 h accounted up to 90%, 95% and 80% of dose administered for 3 group, respectively. Pharmaco-metabolomics analysis revealed urine metabolic trajectory of deviation at 0-1 h or 1-2 h and gradually regressing back to pre-dose group at following time periods. Urine metabolites of M1 to M4 was identified, indicating ethnic difference in metabolites between Chinese or Japanese population. Current work proved safety and tolerance of single-dose administration of oral TBPM-PI in Chinese healthy volunteers over dose of 100-400 mg. All these results provide pharmacokinetics, urine excretion, urine metabolomics, urine metabolites and safety information in healthy Chinese volunteers after oral single ascending doses of TBPM-PI, benefitting further development and clinical utilities.